"Futurizing" smart service: implications for service researchers and managers. Issue 6 (14th September 2015) - Wuenderlich, Nancy V.; Heinonen, Kristina; Ostrom, Amy L.; Patricio, Lia; Sousa, Rui; Voss, Chris; Lemmink, Jos G.A.M.
Abstract : Purpose: – The purpose of this paper is to craft a future research agenda to advance smart service research and practice. Smart services are delivered to or via intelligent objects that feature awareness and connectivity. For service researchers and managers, one of the most fascinating aspects of smart service provision is that the connected object is able to sense its own condition and its surroundings and thus allows for real-time data collection, continuous communication and interactive feedback. Design/methodology/approach: – This article is based on discussions in the workshop on "Fresh perspectives on technology in service" at the International Network of Service Researchers on September 26, 2014 at CTF, Karlstad, Sweden. The paper summarizes the discussion on smart services, adds an extensive literature review, provides examples from business practice and develops a structured approach to new research avenues. Findings: – We propose that smart services vary on their individual level of autonomous decision-making, visibility and embeddedness in objects and customer lives. Based on a discussion of these characteristics, we identify research avenues regarding the perception and nature of smart services, the adoption of smart services, the innovation through smart services as well as regarding the development of new business models. Originality/value: – Smart services is a new emerging topic in service marketing research, their implications on organizations, customers and the service landscape have not been fully explored. We provide a fresh perspective on service research by characterizing relevant aspects of smart service that will stimulate fruitful future research and advance the understanding and practice of smart services.